Assessing Providers' Approach to Hypertension Management at a Large, Private Hospital in Kampala, Uganda - Aliza S. Green; Hayley M. Lynch; Rose Clarke Nanyonga; Allison P. Squires; Darinka D. Gadikota-Klumpers; Jeremy I. Schwartz; David J. Heller (Ubiquity Press, 2020)
Background: Hypertension is increasingly prevalent in Uganda and its clinical management remains suboptimal across the country. Prior research has elucidated some of the factors contributing to poor control, but little is known about providers' approaches to hypertension management and perceptions of barriers to care. This is particularly true in private health care settings - despite the fact that the private sector provides a substantial and growing portion of health care in Uganda. Objective: Our exploratory, pragmatic qualitative study aimed to examine the factors affecting the quality of hypertension care from the perspective of providers working in an urban, private hospital in Uganda. We focused on the organizational and system-level factors influencing providers' approaches to management in the outpatient setting. Methods: We conducted interviews with 19 health care providers working in the outpatient setting of a 110-bed, private urban hospital in Kampala, Uganda. We then coded the interviews for thematic analysis, using an inductive approach to generate the study's findings. Findings: Several themes emerged around perceived barriers and facilitators to care. Providers cited patient beliefs and behaviors, driven in part by cultural norms, as key challenges to hypertension control; however, most felt their own approach to hypertension treatment aligned with international guidelines. Providers struggled to collaborate with colleagues in coordinating the joint management of patients. Furthermore, they cited the high cost and limited availability of medication as barriers. Conclusions: These findings offer important strategic direction for intervention development specific to this Ugandan context: for example, regarding culturally-adapted patient education initiatives, or programs to improve access to essential medications. Other settings facing similar challenges scaling up management of hypertension may find the results useful for informing intervention development as well.